2020
DOI: 10.18844/prosoc.v7i3.5253
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of worksheets supported with prediction-observation-explanation method on high school students opinions

Abstract: The purpose of this study was to investigate the effect of ‘Predict-Observe-Explain’ (POE) activities which is carried out with the help of the POE method worksheets on ‘States of Matter’ in the ninth-grade chemistry course curriculum, on students’ metacognitive awareness. The focus group interview held in this study was conducted with eight students selected from the experimental group on a voluntary basis. Twelve questions were asked to the students. This research is a mixed-method study. While the quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is an interdependent and restricted relationship between the joint positions of human bones. According to the physiological characteristics of human body, the bone length is fixed, so the bone length is calculated and derived according to the coordinates of the obtained data, and the bone position data is constrained and optimized [ 13 ]. The corresponding bone length L obtained by two groups of different Kinect: in calculation and comparison, the length should be consistent.…”
Section: Methodsmentioning
confidence: 99%
“…There is an interdependent and restricted relationship between the joint positions of human bones. According to the physiological characteristics of human body, the bone length is fixed, so the bone length is calculated and derived according to the coordinates of the obtained data, and the bone position data is constrained and optimized [ 13 ]. The corresponding bone length L obtained by two groups of different Kinect: in calculation and comparison, the length should be consistent.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies indicated that the POE technique was an effective tool for enhancing students acquire critical thinking skills, POE activities are enjoyable, and students' abilities improve when taught using the POE strategy (Zakiyah, Widodo & Tukiran, 2020;Yuniar, Sopandi & Sujana, 2020;Banawi, Sopandi & Kadarohman, 2019); Jumiaty, 2017). Based on Karadeniz et al (2020), the students stated that POE activities were simple and easy to follow, and they could easily follow the instructions in each step.…”
Section: Introductionmentioning
confidence: 99%